Managing the supportive care needs of those affected by COVID-19. Issue 4 (23rd April 2020) - Bajwah, Sabrina; Wilcock, Andrew; Towers, Richard; Costantini, Massimo; Bausewein, Claudia; Simon, Steffen T.; Bendstrup, Elisabeth; Prentice, Wendy; Johnson, Miriam J.; Currow, David C.; Kreuter, Michael; Wells, Athol U.; et al.
Globally, the number of people affected by coronavirus disease 2019 (COVID-19) is rapidly increasing. In most (>80%), the illness is relatively mild and can be self-managed out of hospital. However, for about 20%, the illness causes respiratory compromise severe enough to require hospital admission [1]. Patients with severe and critical disease need full active treatment. This may include oxygen for hypoxaemia and ventilatory support, along with optimal management of complications, e.g. super-imposed bacterial infection, and any underlying comorbidities, e.g. COPD or congestive heart failure. To date, no antiviral agent has shown to be effective in treating the disease [2]. For patients with COVID-19, there is a moral obligation to provide good supportive care to prevent avoidable suffering. This article provides a succinct informative overview, clinical guidance and information sheets for both patients and families. https://bit.ly/2UPFsOj